2008
DOI: 10.1021/jp0750708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl and KCl on Phosphatidylcholine and Phosphatidylethanolamine Lipid Membranes:  Insight from Atomic-Scale Simulations for Understanding Salt-Induced Effects in the Plasma Membrane

Abstract: To gain a better understanding of how monovalent salt under physiological conditions affects plasma membranes, we have performed 200 ns atomic-scale molecular dynamics simulations of phosphatidylcholine (PC) and phosphatidylethanolamine (PE) lipid bilayers. These two systems provide representative models for the outer and inner leaflets of the plasma membrane, respectively. The implications of cation-lipid interactions in these lipid systems have been considered in two different aqueous salt solutions, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
266
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 230 publications
(304 citation statements)
references
References 61 publications
38
266
0
Order By: Relevance
“…As we 70 and others 65,67,76,77 have recently demonstrated, small cations such as Na + bind to the ester/carbonyl atoms of phospholipids, inducing a slight enhancement of the lipid order (whereas common counter ions such as Cl À remain firmly in the aqueous phase and do not affect the lipids). Although we have not included ions in these simulations, we expect that the addition of a salt such as NaCl would lead to a systematic ordering effect, identical for all sterols along the series, and therefore all comparative conclusions of this study would be unchanged.…”
Section: View Article Onlinementioning
confidence: 71%
“…As we 70 and others 65,67,76,77 have recently demonstrated, small cations such as Na + bind to the ester/carbonyl atoms of phospholipids, inducing a slight enhancement of the lipid order (whereas common counter ions such as Cl À remain firmly in the aqueous phase and do not affect the lipids). Although we have not included ions in these simulations, we expect that the addition of a salt such as NaCl would lead to a systematic ordering effect, identical for all sterols along the series, and therefore all comparative conclusions of this study would be unchanged.…”
Section: View Article Onlinementioning
confidence: 71%
“…In particular, it has been demonstrated that cations (e.g., Na + ions) are able to penetrate rather deep in the lipid headgroup region. This effect has been observed in zwitterionic, 33,42,46,[50][51][52][53] anionic, 55,56,58 and slightly cationic 61 lipid bilayers. The findings agree with experimental data.…”
Section: Introductionmentioning
confidence: 73%
“…43,45,57 In contrast, using the "Berger lipids", i.e., variants of united-atom force-fields based on refs 70, 96, and 97, tight binding of Na + ions to the lipid carbonyl oxygens is found. 33,42,46,[50][51][52][53]55,56,58,61 Due to the different nature of these two force-fields, simulations using CHARMM27 lipids need to be performed with the area of the bilayer fixed, whereas Berger lipids allow simulations in the NpT ensemble, such that the bilayer can adjust its area to agree with the thermodynamic parameters. Furthermore, the carbonyl region of lipid molecules is more polar in the case of the Berger force-field, so that it attracts cations considerably stronger compared to its CHARMM counterpart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is reminiscent of that found for POPC bilayers in the presence of NaCl, where the distributions of the cations (near the carbonyl/ glycerol region) and anions (displaced into the water phase) set up a capacitor that induces a considerable electric field in the head group region and an overall increase in the water/bilayer electrostatic potential difference. 60,62 Here, instead of residing View Article Online in the chloride atoms, the anionic charge is located in the lipid head groups, but it is still distributed more externally than the cationic charge, and the overall effect is similar.…”
Section: Electrostatic Potentialmentioning
confidence: 99%